The Use Of One Minute Game To Improve Speaking Skills: A Study Of The Eleventh Grade Students At SMA Negeri 7 Palu - Athiya FatinRafifah; Mochtar Marhum; Budi Budi; Abdul Kamaruddin (Hasanuddin University, 2026)
The objective of this research is to prove if the use of One Minute game can improve speaking skill of the eleventh grade students of SMA Negeri 7 Palu. This research used quantitative method with a pre-experimental research design. The population of this research was the eleventh grade students of SMA Negeri 7 Palu with the total of 351 students. The sample of this research was XI 7 with 34 students, the pre-experimental group was selected by using a purposive sampling technique. The pretest was used to measure students' speaking abilities before treatment and the posttest was carried out to measure students' speaking abilities after treatment. The data analysis indicates that there is a slightly significant increase between the pretest and posttest results. The student's mean score before given treatment was 29.77. After giving the treatment, the mean score of the students in posttest was 62.13. By applying a significant level of 0.05, the researcher found that the value of the t-counted (15.97) was higher than t-table (2035). In conclusion, the use of one minute game is effective in improving students speaking skills of eleventh grade of SMA Negeri 7 Palu. Based on the result, It was proved that the hypothesis is accepted which means there is improvement in the students speaking skills after being given the treatment. It means that the One Minute game can improve students’ speaking skills.